If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-6y) + -4 = 16 Reorder the terms: -4 + (-6y) = 16 Solving -4 + (-6y) = 16 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + (-6y) = 16 + 4 Combine like terms: -4 + 4 = 0 0 + (-6y) = 16 + 4 (-6y) = 16 + 4 Combine like terms: 16 + 4 = 20 (-6y) = 20 Divide each side by '-6'. y = -3.333333333 Simplifying y = -3.333333333
| 90/0.09*10 | | 9(2a+4b-7c)-4(b+c)-7(-c-4b)= | | 8y^2-12=0 | | 3(p-2p)-4(2p-3q-5)= | | 5(y-2)=4(2y+5) | | 6x+5=3x+15 | | 9(2a+5)= | | 16c-4pt= | | H=90+15t-5t^2 | | 17-4a=3a-4 | | 6x-9=x+3 | | 9x+40xyz+5+100xyz-5x+15+2x-50xyz= | | 100-k=k-342 | | K-45=395-k | | 37-(5-3x)=0 | | 5x/48=2 | | 2r+3b=18 | | 12+y=-y-36 | | 4r(r+4)=33 | | s*4+26=90 | | 55-5y=13-3y | | 27-8x=13-5x | | 2.4+2x=0.2 | | 14=6C-4WHATISC | | 5y+3=y-5 | | 10x+9y+5z=0 | | 8(n+3)= | | X-5=2x+3-(x-2) | | 8p-8i+8p+3i= | | 9➖3➗1/3➕1- | | 100/110*100=9*1/11 | | 100/110*100 |